Inwieweit stimmt die Ergebnisbeurteilung nach Eingriffen bei Beugesehnenverletzungen bei Anwendung der Bewertungssysteme nach Buck-Gramcko, Strickland und der Amerikanischen Gesellschaft für Handchirurgie überein? - Hahn, Peter; Kirchberger, Michael Constantin; Unglaub, Frank; Spies, Christian (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2016)
Purpose: Scores are essential for comparing function after flexor tendon reconstructions. The Buck-Gramcko Score, the Strickland Score and the ASSH (American Society for Surgery of the Hand) Score are the most commonly applied rating systems. The purpose of this study is to evaluate these systems and their interchangeability. Method: Based on an unrestricted metacarpophalangeal (MCP) joint of 0-0-90° or limited range of motion of the MCP joint of 0-30-90°, the scores of the 3 rating systems were assessed and graphically displayed for each possible finger position regarding proximal (PIP) and distal (DIP) interphalangeal joints. Results: Based on an unrestricted MCP joint, the scores of the 3 rating systems differed in 24-33% of the obtained values, depending on the sum of joint flexion and extension deficits of the aforementioned PIP and DIP joints. If the range of motion was restricted to 0-30-90° in the MCP joint, differing values were only observed in 16-19% of the obtained values. In extreme cases, scores for the same clinical presentation may thus be “excellent”, “fair” or “poor”, depending on which system has been used. Conclusion: The different rating systems for the evaluation of flexor tendon reconstruction are neither identical nor adjustable. Therefore, consensus or at least a recommendation is needed regarding the system to be used. It may even be necessary to develop a generally accepted rating system to compare studies. In the meantime, the readings of the active and passive range of motion of all joints of the affected finger/thumb ought to be published in studies to compare and validate the results.
Gesehen am 18.07.2019